Desenvolvimento de procedimentos e métodos analíticos no campo forense aplicando os princípios da química verde - Luiz, Vitor Hugo Marques [UNESP] (2016)
This work describes the development of analytical methods for the quantitative determination of furosemide and bumetanide in urine samples using diffuse reflectance spectroscopy (for furosemide) and scanning imaging with quantification by color histogram using RGB color pattern (for both). It involves also the development of a quantitative method for the detection of lead in gunshot residues (GSR) in the hands of the shooters using bacterial cellulose membranes as substrate collection, aiming the discovery of shooting time. It is also done the quantification of lead in progressive hair lotions samples using a previously developed method, aiming the detection of products adulterations and quality control. It also studies the potentiality of the usage of bacterial cellulose membranes for the collection of fingerprints. The developed methods are consisted in the reaction of furosemide (FUR) with the cromogenic reagent p-dimethylamino cinnamaldehyde (p-DAC) 0.70% and hydrochloric acid (HCl) 1.72 mol L-1 in qualitative filter papers with hydrophobic barrier, with spectrophotometric detection and by color histogram; in the reaction of lead(II) ion (Pb2+) with sodium rhodizonate (ROD) 0.16% in micellar medium of sodium dodecyl sulfate (SDS) 5 mmol L-1 in bacterial cellulose membranes with spectrophotometric detection and by scanning electron microscopy; in the reaction of bumetanide (BMT) with the reagent p-dimethylamino cinnamaldehyde (p-DAC) 0.6% and hydrochloric acid (HCl) 0.27 mol L-1 in qualitative filter papers with hydrophobic barrier with color histogram detection an in the collect of fingerprints using bacterial cellulose membranes impregnated with ninhydrine, silver nitrate or zinc oxide, of which the silver nitrate and ninhydrin acted as reasonable collection agents. All concentrations were optimized through chemometrics designs. The reactions were carried out as spot test, involving the formation of a colored product at 545 nm for lead, in 585 nm for furosemide and in 520 nm for bumetanide. Analytical curves were built from standard solutions of the respective analytes. The methods developed for furosemide and bumetanide were applied in fortified synthetic and natural urine samples and the results obtained were compared statistically with comparative methods. The validation of the methods were performed by standard addition and recovery and by comparison of methods, for FUR and BMT, yielding recoveries between 98.0 and 115.3% for furosemide quantification methods and between 93.0 and 102.0% for the quantification method for bumetanide. GSR collection method is based on the use of thin membranes of bacterial cellulose developed by Photonic Materials Group IQ-UNESP. For GSR, 40 total collections were carried out in known and different times of collection after shooting times and their comparison through analytical curves were done, showing the possibility of the detection of the shooting time with an error of 5 minutes, approximately. The results were statistically compared and the values obtained from statistical tests showed that the methods can be used for routine analysis in forensic laboratories.